2010
DOI: 10.3329/jhpn.v28i2.4880
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Tuberculosis: Perspectives and Experiences of the People of Sabah, East Malaysia

Abstract: Malaysia is a country with the intermediate burden of tuberculosis (TB). TB is still a public-health problem in Sabah, one of the two states in East Malaysia. In 2007, the state of Sabah contributed slightly more than 3,000 of 16,129 new and relapse cases reported in the country. It has a notification rate of two and a half times that of the country's. Very few studies on TB have been conducted in Sabah, and there is little documentation on the perceptions of TB patients and the community about TB, healthcare-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 11 publications
6
37
0
4
Order By: Relevance
“…In study done by Paz-Soldán et al also reported that parents of child were really selective in disclosing the condition of their children and parents who disclosed the child condition to other family member got tremendous love and care that helped lot in completing the treatment of child. [11] In agreement with other studies, [10][11][12] the suffering experienced by these participants was primarily linked to the likelihood of being discriminated against, which made them feel stigmatized. Despite TB being a curable disease, many professionals' different streams such as psychologists, anthropologists, sociologists, and TB analysts have repeatedly indicated that talking about the disease still causes discomfort and unease.…”
Section: International Journal Of Medical Science and Public Healthsupporting
confidence: 79%
“…In study done by Paz-Soldán et al also reported that parents of child were really selective in disclosing the condition of their children and parents who disclosed the child condition to other family member got tremendous love and care that helped lot in completing the treatment of child. [11] In agreement with other studies, [10][11][12] the suffering experienced by these participants was primarily linked to the likelihood of being discriminated against, which made them feel stigmatized. Despite TB being a curable disease, many professionals' different streams such as psychologists, anthropologists, sociologists, and TB analysts have repeatedly indicated that talking about the disease still causes discomfort and unease.…”
Section: International Journal Of Medical Science and Public Healthsupporting
confidence: 79%
“…[18,20] Patients who were not adequately educated about the cause of TB, and who felt embarrassed about having contracted the disease, combined with negative attitudes on the part of healthcare staff, discouraged them from seeking early treatment. [10] Tests such as chest X-rays and sputum analysis, which are accepted to be part of the standard care of practice in the national healthcare system, [3,11] were not conducted in all participants in our study. It is possible that participants who could not produce sputum were sent for alternative tests.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The risk of developing TB among HCWs depends on factors such as occupational category, age and use of TB infection control measures in the workplace. [7] While a number of general population studies have been conducted globally on the attitudes and psychological impact of contacting TB, [4,[8][9][10] little or no work has been done among HCWs generally, and particularly among doctors who are at greater risk of exposure than the general population. A qualitative study on the impact of drug-resistant TB on 5 medical doctors in SA found that 4 of them experienced adverse effects owing to medication, which in some continued for several years after treatment was completed.…”
mentioning
confidence: 99%
“…9,10,[25][26][27]30,31,34,35,[37][38][39][40]42,49,55,58,71,[74][75][76][77][78] Patients with TB often consult traditional healers in Gambia, 74 South Africa, 40 Uganda, 10 Thailand, 77 Malaysia 76 and the Philippines. 78 Traditional herbal medicine is used by Samoans in the United States.…”
Section: Treatment and Health Responses To Tuberculosismentioning
confidence: 99%